L'enquête publique et le pouvoir de condamnation pour outrage au tribunal - Crête, Raymonde (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
In the sphere of public inquiries, i.e. those which are limited to the exercice of the power of inquiry and recommendation to a higher instance, the Quebec legislator has enacted different provisions conferring upon the investigators the power to punish acts of contempt. Such provisions were necessary because investigators, as opposed to judges of the superior courts and the courts of records, possess no inherent capacity to impose penalties for acts of contempt committed in or out of their presence. To this end, the legislator has conferred upon investigators the power to condemn for contempt of court, by provisions which refer to the powers of the Superior Court in this matter. The investigators therefore may punish acts of contempt committed in their presence, such as witnesses' refusal to testify or produce documents. It is however more difficult to determine if the investigators are empowered to punish acts of contempt committed outside their presence, for usually inferior courts are not so empowered. In this connection, the courts have also examined the nature of contempt, which can be either civil or criminal depending on the nature of the jurisdiction exercised and the offence committed. With respect to public inquiries, it is equally interesting to ask oneself if the investigators can use contempt of court as a means of punishment. Relative to this question, we think that the investigators should sanction contempt only as a coercive means and not as punishment. Upon conviction of contempt, it is important that the convicted parties have some recourse, since the decisions may have serious consequences such as a fine or imprisonment. In this regard, the courts agree to exercice their powers of control when commissioners exceed their jurisdiction. There is however no right to appeal the commissioner's decision. Investigators may conceivably use such vast powers in an arbitrary and abusive manner. In a perspective of legislative reform, we would be of the opinion that it would be preferable to attribute such a power to a court of justice rather than to the investigators themselves.